TAHLĪL MA’RIFATI AL-MUḤTAWA AL-TIKNŪLŪJIY AL-TARBAWIY LI MU’ALLIMĪ AL-LUGAH AL-‘ARABIYYAH AL-MIHNIYYIN FI TAṬWĪR ADAWĀT AL-TA’ALLUM - Ahmad Taufiq; Arrum Wijaya; Mujeeb Khan Saqafi (ALSINATUNA, 2023)
In 21st century learning, there is a framework that can be used to determine a teacher's ability to prepare a Learning Implementation Plan (RPP), namely the TPACK framework. Based on research conducted by previous researchers, the results show that there are still many teachers who have low TPCK, and don't even know TPACK. Therefore, this research aims to describe the preparation of lesson plans for class XI mufradāt material at Ma'arif NU Kajen Vocational School, Pekalongan Regency to be able to describe the TPACK of Arabic teachers in preparing mufradāt learning plans. This type of research is qualitative research using field research methods carried out at Ma'arif NU Kajen Vocational School, Pekalongan Regency. Based on the research results, it can be concluded that (1) The preparation of lesson plans for class (2) TPACK competency of classroom Arabic teachers XI at Ma'arif NU Kajen Vocational School, Pekalongan Regency is at the recognizing level, because teachers can utilize ICT innovation and see the arrangement of ICT innovation with content but do not coordinate innovation in their learning.